PENGARUH PERUSAHAAN KELUARGA DAN PERAN KOMISARIS INDEPENDEN TERHADAP MANAJEMEN LABA (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2022) - Novita, Trias Inggar; Fuad, Fuad (Diponegoro Journal of Accounting, 2024)
This research aims to examine the influence of family companies and independent boards of commissioners on earnings management. The independent variables used in this research are family companies and independent boards of commissioners. Control variables use company size, leverage, and company operating cash flow. Meanwhile the dependent variable is earnings management.The sample for this research is manufacturing companies in the consumer goods industrial sector listed on the Indonesia Stock Exchange during the 2021-2022 period. The research sampling method uses purposive sampling technique. The analysis technique used is multiple regression analysis technique.The results of this research show that only one hypothesis is supported, namely that an independent board of commissioners has a negative effect on earnings management, while the other hypotheses are not supported. Family companies have no influence on earnings management and independent boards of commissioners have no influence on family companies and earnings management.